Vishnu Temple and Shiva Temple behind the Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Chandrabhaga temple complex has two temples, a Vishnu Temple (left) and a Shiva Temple (right), situated on their respective platforms behind the Sitaleshwar Temple. Both temples presently consist only of the garbhagriha (sanctum sanctorum), which can be accessed by a set of steps.